Extending the LoRa Direct-to-Satellite Limits: Doppler Shift Pre-Compensation - Muhammad Asad Ullah; Richard Demo Souza; Gianni Pasolini; Jean Michel de Souza Sant'Ana; Marko Hoyhtya; Konstantin Mikhaylov; Hirley Alves; Enrico Paolini; Akram Al-Hourani (IEEE Open Journal of the Communications Society)
Earlier studies and field tests have extensively investigated Long Range (LoRa) direct-to-satellite (DtS) communications, confirming the feasibility of integration with Low Earth Orbit (LEO) satellites. These works identify the Doppler effect as one of the primary challenges. Therefore, there is a need for a robust solution to mitigate the impact of this phenomenon in order to improve the performance of LoRa DtS communications in a LEO scenario. This paper addresses this shortcoming by developing a solution to pre-compensate the Doppler shift. Specifically, we propose a method that allows end devices to estimate and pre-compensate the Doppler shift before initiating an uplink transmission. This framework, which requires satellites to broadcast Doppler Beacons, ensures compatibility with existing LoRaWAN end devices without requiring any hardware modifications. We leverage data from real-world LoRa satellites’ empirical telemetry to validate our proposed method. We analytically study packet losses due to Doppler shift across different carrier frequencies, specifically 401.5 MHz, 868 MHz, and 2 GHz. Our analysis also considers different satellite orbital heights, specifically 200 km and 518 km, as well as channel bandwidths of 31.25 kHz, 62.5 kHz, and 125 kHz. Our results demonstrate that the proposed solution effectively pre-compensates for the Doppler shift and mitigates the packet losses, extending the passing satellites’ effective visibility window duration. We examine the maximum Doppler shift in the communication channel and the calculate required Doppler Beacon bandwidth for different orbital altitudes, minimum elevation angles, and carrier frequencies. This study also investigates how the proposed framework affects the battery lifetime of the end device, showing a marginal decrease of 2.5% compared to traditional LoRaWAN operation.